OPTIMISASI PERANCANGAN PEREKAHAN HIDRAULIK PADA RESERVOIR GAS YANG BERPERMEABILITAS RENDAH - Iwan
Hydraulic cracking is a way to provide stimulation to the reservoir to increase productivity. Low permeability reservoir is a right target for hydraulic fracturing. Fracturing activity requires economic consideration factors such as costs and revenues that will be earned. Selection of the proper design is the key to success this fracturing job. In this study, we sensitivity varying lengths of fractures to conduct their effects on the net present value (NPV). A methodology was developed to determine the effect of the length of the fracture caused by the design of the to NPV and production period. Various information is also used to support and run this study. Reservoir property information, the configuration of the well, the mechanics of fracturing, fracture geometry model selection and economic data became the basis for calculating in this study. From the simulation results using a simulator, the optimum design of fracturing can be determined by considering the best NPV of each fracture length. Best design fracture length is the length of cracks that can provide the greatest NPV. Other parameters such as recovery increment and production period can be determined through the results of this simulation.